حكم رواية المبتدعين عند المحدثين - Mohd Fauzi Mohd Amin; Khairul Anwar Muhammad Al-Bakri (Universiti Sains Islam Malaysia, 2024)
This working paper discussed regarding the law of narrating "hadith" among the members of "bid'ah" in the eyes of the members of "hadith". Narrating "hadith" is a noble work and very important in maintaining the validity of Rasullulah's "hadith" from those which are "daif'. The hadith's theologians have put on a very meticulous effort in the process of narrating "hadith", and they have outlined a guideline, which need to be followed in facing the narration by the members of "bid'ah". Therefore, the discussion is aiming at the meaning of bid'ah itself, a person who does things, whch are bid'ah and the category of bid'ah. Apart from that, this working paper classified the "bid'ah" into two, which are, one that brings to the "kufur" and the other that brings to the "fasik". At the end, the writer found that if the narrator had done the bid'ah which lead to the "kufur", the narration is rejected, and if the bid'ah leads to the "fasik", the "ulamak" make the evaluation whether to accept it or not.